(untitled) (Research, Society and Development, 2021)
This study aims to integrate geographic, social and health analyses considering the variables race/color, for understanding the complexity of territorialization of mental health care. For this, it proposes to answer the following question: what are the sociodemographic characteristics of the territory occupied by children, women and adolescents in the area covered by CAPSij Brasilândia? Methodology: Sectional study that allows analysis and evaluation of collective health risks to which a population is exposed, particularly socioeconomic and environmental risks. The georeferencing describes and allows the visualization of spatial distribution, marking social determinants and etiological factors that can formulate hypotheses and point out associations between the phenomena. With the GIS technology we sought to delimit the area of coverage of the service, as well as, to classify what we call by complexities for territorialization of mental health care. Results: The spatial distribution of families (black women, children and adolescents), accompanied by CAPSij shows the territorial segregation experienced by the poor and black population. The territories occupied by the majority of the black population are portraits of the racism that structures the Brazilian social fabric. Conclusion: territories are products of social relations, and can confer advantages and disadvantages related to location, infrastructure, mobility, education, work, health, culture, etc. This reality shapes the mental health processes of the black population. This study on the spatial variation in the race/color clipping in public health services allows us to see how racial inequalities impact access to the right to health, and to point out interventions from the perspective of human rights.